Coinfection with HIV-1 skews iNKT cells toward TCR anergy and limited expansion potential in people with hepatitis C - Nettere, Danielle; White, Scott; Williams, Grant; Jha, Shalini; Moody, M. Anthony; Chan, Cliburn; Ferrari, Guido; Naggie, Susanna (Frontiers in Immunology, 2025)
IntroductionHepatitis C virus (HCV) infection remains a leading cause of morbidity and mortality in people with human immunodeficiency virus (HIV). Liver fibrosis progression is more rapid in people with HIV/HCV coinfection compared to HCV monoinfection and the rate of resolution of liver fibrosis after HCV cure is unknown in people with HIV. Invariant natural killer T (iNKT) cells are enriched in the liver and play important roles in initiating immune responses to hepatotropic pathogens and promoting healing following injury. It was recently reported that the pro-healing CD4+ iNKT cells are preferentially infected and depleted in early HIV infection, but this effect on HCV-related liver disease outcomes is unclear.MethodsHere we examined and compared peripheral blood iNKT cells from people with HIV/HCV coinfection and people with HIV and HCV monoinfection or no infection (controls). We evaluated the iNKT cells’ expansion potential and phenotype using an unbiased Uniform Manifold Approximation and Projection (UMAP) and clustering based approach.ResultsWe observed that circulating iNKT cells from people with HIV and HIV/HCV coinfection have impaired expansion to T-cell receptor (TCR) stimulation. We also observed an enrichment of the CD8+ and CD57+ iNKT subsets, which are thought to represent terminally differentiated iNKT cells. HCV monoinfection on the other hand minimally impacted iNKT phenotypes compared to controls.DiscussionThe changes observed in iNKT phenotype and proliferative ability in people with HIV/HCV coinfection suggest an impairment that may be contributing to the enhanced pathogenesis during coinfection and could inform novel therapeutic approaches.